The influence of labor taxes on the migration of skilled workers - Peter Egger; Doina Maria Radulescu (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper investigates empirically the role of taxes on labor for the stock of expatriates and the migration flows of skilled workers. Given the increasing mobility of labour, especially of high-skilled people and expatriates, it is interesting to see to what extent labour income taxes and social security contributions determine migration flows. We collect data on personal income tax profiles for 49 economies and the year 2002. In particular, we determine the component of labor taxes which is borne by employers and the one that is borne by employees, following the OECD's Taxing Wages Approach. For the latter, we calculate the progressivity of personal income tax rates between the average wage and five times the average wage. This may be interpreted as the tax progression which is relevant for well-paid workers. Then, we use the personal income tax variables to estimate their effect on bilateral stocks of expatriates into OECD countries and the migration of skilled workers into these countries. Personal income tax rates turn out to have a robust negative effect on cross-border flows of skilled workers in the OECD.
Keywords: J61; H24; F22; 330; Labor taxation; skilled workers; migration; expatriates; Lohnsteuer; Sozialversicherungsbeitrag; Steuerbelastung; Internationale Arbeitsmobilität; Hochqualifizierte Arbeitskräfte; OECD-Staaten